Understanding the investigators: a qualitative study investigating the barriers and enablers to the implementation of local investigator-initiated clinical trials in Ethiopia - Franzen, SR; Chandler, C; Enquselassie, F; Siribaddana, S; Atashili, J; Angus, B; Lang, T (BMJ Publishing Group, 2013)
OBJECTIVES: Clinical trials provide 'gold standard' evidence for policy, but insufficient locally relevant trials are conducted in low-income and middle-income countries. Local investigator-initiated trials could generate highly relevant data for national governments, but information is lacking on how to facilitate them. We aimed to identify barriers and enablers to investigator-initiated trials in Ethiopia to inform and direct capacity strengthening initiatives. DESIGN: Exploratory, qualitative study comprising of in-depth interviews (n=7) and focus group discussions (n=3). SETTING: Fieldwork took place in Ethiopia during March 2011. PARTICIPANTS: Local health researchers with previous experiences of clinical trials or stakeholders with an interest in trials were recruited through snowball sampling (n=20). OUTCOME MEASURES: Detailed discussion notes were analysed using thematic coding analysis and key themes were identified. RESULTS: All participants perceived investigator-initiated trials as important for generating local evidence. System and organisational barriers included: limited funding allocation, weak regulatory and administrative systems, few learning opportunities, limited human and material capacity and poor incentives for conducting research. Operational hurdles were symptomatic of these barriers. Lack of awareness, confidence and motivation to undertake trials were important individual barriers. Training, knowledge sharing and experience exchange were key enablers to trial conduct and collaboration was unanimously regarded as important for improving capacity. CONCLUSIONS: Barriers to trial conduct were found at individual, operational, organisational and system levels. These findings indicate that to increase locally led trial conduct in Ethiopia, system wide changes are needed to create a more receptive and enabling research environment. Crucially, the creation of research networks between potential trial groups could provide much needed practical collaborative support through sharing of financial and project management burdens, knowledge and resources. These findings could have important implications for capacity-strengthening initiatives but further research is needed before the results can be generalised more widely.